Prenatal Immunity and Influences on Necrotizing Enterocolitis and Associated Neonatal Disorders - Sampah, Maame Efua S.; Hackam, David J. (Frontiers in Immunology, 2021)
Prior to birth, the neonate has limited exposure to pathogens. The transition from the intra-uterine to the postnatal environment initiates a series of complex interactions between the newborn host and a variety of potential pathogens that persist over the first few weeks of life. This transition is particularly complex in the case of the premature and very low birth weight infant, who may be susceptible to many disorders as a result of an immature and underdeveloped immune system. Chief amongst these disorders is necrotizing enterocolitis (NEC), an acute inflammatory disorder that leads to necrosis of the intestine, and which can affect multiple systems and have the potential to result in long term effects if the infant is to survive. Here, we examine what is known about the interplay of the immune system with the maternal uterine environment, microbes, nutritional and other factors in the pathogenesis of neonatal pathologies such as NEC, while also taking into consideration the effects on the long-term health of affected children.